Clinical, Demographic, and Laboratory Profile of Pediatric Meningitis at Benghazi Pediatric Hospital, Libya: A Retrospective Study - Busba , Abdelnaser; Abusneina, Abdelmuhsen; Albadry , Muna; Aldrsy, Mohammed; Alfaitory , Ahmed; Alsaity , Moath (Libyan Journal of Medical and Applied Sciences, 2026)
Background: Meningitis affects more than 2.5 million people annually and disproportionately burdens pediatric populations, particularly in low- and middle-income countries. Libya lacks comprehensive, up-to-date clinical data on pediatric meningitis, limiting evidence-based interventions. To characterize the demographic, clinical, and laboratory profiles of children diagnosed with meningitis at Benghazi Pediatric Hospital, Libya, in 2024, and to assess disease outcomes, including mortality. Materials and Methods: A retrospective descriptive study was conducted involving 101 children aged 0–10 years diagnosed with meningitis during 2024. Data were manually extracted from paper-based medical records and analyzed using descriptive statistics including frequencies, percentages, means, and standard deviations. Results: Infants aged 3 to <12 months constituted the largest group (47.5%), with male predominance (62.4%). Fever was present in 84.2% of cases and vomiting in 51.5%. Elevated CSF WBC counts were observed in 68.3% of cases. CRP >50 mg/L, indicating likely bacterial infection, was found in 20.8% of patients. CSF bacterial culture was positive in only 2.0% of cases, attributed to prior antibiotic use. The overall mortality rate was 5.9%. Comorbidities were present in 51.5% of cases. Conclusion: Pediatric meningitis in Benghazi predominantly affects infants under one year, with significant inflammatory markers and moderate mortality. These findings underscore the need for enhanced vaccination coverage, improved molecular diagnostics, early empirical treatment, and structured survivor follow-up in Libyan pediatric hospitals.